The Effect of Service Effectiveness and MSME Business Capital Financing on Customer Satisfaction at Bank BTN Sub-Branch Office Rancaekek - Aprilliani, Devi; Sari, Widya (Journal of Applied Islamic Economics and Finance, 2025)
Based on the observation results, the background of this research is the fluctuation in the number of MSME financing customers at Bank BTN KCP Rancaekek, accompanied by complaints regarding the speed and accuracy of service, level of comfort, limited facilities, low flexibility, and lack of digital innovation. These conditions affect customer satisfaction and are driven by the bank’s selective fund distribution policy as an effort to maintain financial stability and soundness This research aims to determine the effect of service effectiveness and MSME financing on customer satisfaction, both partially and simultaneously, at Bank BTN KCP Rancaekek. The object of this research is the MSME financing customers at Bank BTN KCP Rancaekek. The type of research is quantitative associative, using primary data collected through observation, interviews, literature study, and questionnaires. The sampling method in this study uses probability sampling with a simple random sampling technique. The population in this research consists of all MSME financing customers totaling 788 people, with a sample of 266 respondents. The tools for testing and data analysis, as well as hypothesis testing, include validity testing, reliability testing, data normality testing, multiple regression analysis, multiple correlation analysis, coefficient of determination analysis, t-test, and F-test. The results of this study indicate that the effectiveness of services and Value MSME financing significantly affects the satisfaction of customers of Bank BTN KCP Rancaekek. The t-test results prove that the effectiveness of services tcount > ttable (6.394 > 1.969) and Value MSME financing tcount > ttable (16.867 > 1.969) each has a significant effect with R² of 13,4% and 45,5%, respectively. The F-test simultaneously Fcount > Ftable (226.020 > 3.03) shows a significant influence of both on customer satisfaction of 63,2%.